2016
DOI: 10.18632/oncotarget.7242
|View full text |Cite|
|
Sign up to set email alerts
|

Pinin interacts with C-terminal binding proteins for RNA alternative splicing and epithelial cell identity of human ovarian cancer cells

Abstract: Unlike many other human solid tumors, ovarian tumors express many epithelial markers at a high level for cell growth and local invasion. The phosphoprotein Pinin plays a key role in epithelial cell identity. We showed that clinical ovarian tumors and ovarian cancer cell lines express a high level of Pinin when compared with normal ovarian tissues and immortalized normal ovarian surface epithelial cell lines. Pinin co-localized and physically interacted with transcriptional corepressor C-terminal binding protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 50 publications
4
34
0
Order By: Relevance
“…Higher PNN mRNA and/or Pinin protein expression levels were observed in tissues from ovarian carcinoma, hepatocellular carcinoma and CRC compared to the relative matched normal mucosa tissues. In these studies, high levels of PNN and/or Pinin were also associated with poor prognosis . A role of PNN in epithelial–mesenchymal transition has been suggested.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Higher PNN mRNA and/or Pinin protein expression levels were observed in tissues from ovarian carcinoma, hepatocellular carcinoma and CRC compared to the relative matched normal mucosa tissues. In these studies, high levels of PNN and/or Pinin were also associated with poor prognosis . A role of PNN in epithelial–mesenchymal transition has been suggested.…”
Section: Discussionmentioning
confidence: 92%
“…However, more recently, studies performed also in other cancers suggested a role of PNN in prognosis and in resistance to chemotherapy . Higher PNN mRNA and/or Pinin protein expression levels were observed in tissues from ovarian carcinoma, hepatocellular carcinoma and CRC compared to the relative matched normal mucosa tissues. In these studies, high levels of PNN and/or Pinin were also associated with poor prognosis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following these early studies, CtBP1 overexpression has been observed in a number of different cancers, including prostate (64, 68), melanomas (69), colon (70), leukemia (7173), ovarian (74, 75), and breast cancer (76, 77), among others. In most cases CtBP1 overexpression is pro-tumorigenic.…”
Section: The Ctbp Co-repressors Play Multiple and Context-dependent Rmentioning
confidence: 97%